SEXUAL ACTIVITY-THEME PROFANITIES IN COMPLIMENT SPEECH ACTS ON TWITTER (MAKIAN BERTEMAKAN AKTIVITAS SEKSUAL DALAM TINDAK TUTUR MEMUJI DI TWITTER) - Putri, Aprilia Kartika; Oktavianus, Oktavianus; Marnita, Rina (Jurnal Gramatika, 2019)
The problem in this research is that rarely profanities used and understood as language forms to express compliments. This research paper aims to describe the linguistic forms, pragmatic meanings, and pragmatic functions of sexual activities-theme profanities in compliment speech acts on Twitter. Theories from Kreidler (2002), Ljung (2011), and Almos (2013)were used in this study. The observational method was used to collect the data. Distributional and identity methods were used to analyze the data. The results of this study demonstrate: (1) linguistic forms of the sexual activity-theme profanities are words, (2) the pragmatic meaning of the sexual activity-theme profanities is as utterance meaning, and (3) the pragmatic functions of the sexual activity-theme profanities are as adverbial and adjectival intensifier, expletive, noun support, and emphasis. This research hopefully can help EFL (English as a Foreign Language) students avoid misunderstanding while communicating in English with other English speakers on Twitter.